2007
DOI: 10.1099/jmm.0.47114-0
|View full text |Cite
|
Sign up to set email alerts
|

Racemoside A, an anti-leishmanial, water-soluble, natural steroidal saponin, induces programmed cell death in Leishmania donovani

Abstract: Leishmaniasis remains a major health problem of the tropical and subtropical world. The visceral form causes the most fatalities if left untreated. Dramatic increases in the rates of infection and drug resistance and the non-availability of safe vaccines have highlighted the need for identification of novel and inexpensive anti-leishmanial agents. This study reports that racemoside A, a water-soluble steroidal saponin purified from the fruits of Asparagus racemosus, is a potent anti-leishmanial molecule effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 23 publications
4
44
0
3
Order By: Relevance
“…DNA content was analyzed by flow cytometry as described previously (12). Briefly, parasites (1 ϫ 10 7 promastigotes/ml) were incubated with or without 50 and 100 M SQ in culture medium for 24 h at 28°C, washed twice with PBS, fixed with ice-cold methanol by incubation for 3 min on ice, resuspended in 500 l of PBS containing 1 g/ml PI and 100 g/ml RNase A, and incubated for 1 h in the dark at room temperature.…”
Section: ؉mentioning
confidence: 99%
“…DNA content was analyzed by flow cytometry as described previously (12). Briefly, parasites (1 ϫ 10 7 promastigotes/ml) were incubated with or without 50 and 100 M SQ in culture medium for 24 h at 28°C, washed twice with PBS, fixed with ice-cold methanol by incubation for 3 min on ice, resuspended in 500 l of PBS containing 1 g/ml PI and 100 g/ml RNase A, and incubated for 1 h in the dark at room temperature.…”
Section: ؉mentioning
confidence: 99%
“…In the present study, the fleawort extract showed no obvious anti-leishmanial activity, while the two others, namely the tarragon and savory extracts, showed a significant anti-leishmanial effect. Studies showed that a number of herbs have moderate to strong anti-leishmanial activity (Dutta et al 2007;Cruz-Ede et al 2013;Rodrigues et al 2014;Azizi et al 2014;Nosratabadi et al 2015). Some authors found that a few plants can be used as an adjuvant in vaccination against Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…At each interval (6,24,48, and 72 hours), 10 µL of each sample was gently mixed with 10 µL of 0.4% trypan blue on a glass slide. The mortality of parasites was determined by counting the number of alive (not stained) and dead (stained) promastigotes according to the following formula (1).…”
Section: Experimentationmentioning
confidence: 99%